AS QUATRO OPERAÇÕES NUMÉRICAS E SUAS INVERSAS NO ENSINO FUNDAMENTAL: CONTRIBUIÇÕES DE UM JOGO DIDÁTICO COM SITUAÇÕES-PROBLEMA - Cezar, Ana Maria de Lima (2021)
This work presents and discusses the results of a research developed in the context of the Graduate Program in Science and Mathematics Teaching at the Franciscana University, in the line of research Teaching and Learning Mathematics. The main objective of this Master's work in the professional modality was to analyze a digital educational game, with problem situations involving the four numerical operations and their inverses, can contribute to overcoming the mathematical difficulties in the transition from the early years to the final years of education fundamental. As a methodology, a qualitative research was used, seeking to understand how a digital educational game can contribute to the meaningful learning of students in a dynamic and inductive way, seeking to verify the difficulties faced by them in the problem-situations contained in the game. Drawing on theoretical support for studies by Onuchic (1999), Poffo (2011), Leal Jr and Onuchic (2015), about the resolution of problems about the use of digital games as a learning tool, contained in studies by Kishimoto (1996), Fernandes (2010), this work was based on the ideas of Vygotsy (1999) about the importance of the game in learning, especially in mathematics education. This theoretical survey served to analyze the application of a diagnostic research with students of a private school, located in the city of Santiago/RS, applied to students from the 5th to 9th grade of elementary school, in order to identify the level of knowledge of students involved in the research in relation to problem situations involving the four numerical operations and their inverses. Based on the collected data, it is observed that the students had difficulties in interpreting problem situations involving the operations of subtraction, division and their inverses. Through diagnostic research, it was possible to verify these difficulties, especially when the question's statement referred to finding one of the subtraction or division terms through its inverses. The theoretical reference, together with the results obtained in the diagnostic evaluation, served as support material for the construction of an educational product, called “Numeric Trail”. It is a digital educational game, built in a track format, where the student evolves and is rewarded as he succeeds in solving certain problems. Based on the analysis of the collected data, it was possible to verify that the game “Numeric Trail” was positive, as among the plays some students reported their doubts with questions about the issues for their colleagues and the teacher, clearing their doubts, hitting and concluding the Game levels with joy and satisfaction. In the search to win the game, the student develops strategies to solve problem situations, analyzing mathematical concepts, investigating the possibilities of overcoming opponents, remaking his reasoning, promoting the educational process. To assess the acceptance of the educational product, a satisfaction survey was carried out among students, where the importance of the game to assist and help in the students' meaningful learning was evident. Regarding the teaching of mathematics, it is important and necessary to promote changes, developing strategies that favor the construction of logicalmathematical reasoning of students. Such strategies can be constituted respecting the particularities and differences promoted by the stages of development in which children and young people are and considering the needs of each subject, but directing them to a single objective: learning.